Visual (Visual Perception) Content Syncretism in Qualities Related to Intuition - Teshaboeva Gulnoza (Global Scientific Publishing, 2024)
It is known that knowledge of the universe human sensory organs and emotions are manifested through synesthetic cognition.Emotional perception, on the other hand, is realized in the knowledge of sight, hearing, touch, taste and smell. Therefore, our sensory organs are considered important in the functioning of human life, in the way they live. R.G.Podolny told the senses: "why do we need to study the sensory organs? puts the question of scientist. It is then that the sensory organs are the most important tool in obtaining more accurate information about the external world and the changes that take place in it, if possible in understanding the universe.” 1 Such perception is called emotional perception. Also, in psychology, the term intuition is much mentioned, and the definition given to it, annotations, are also Turlich. The source of knowledge, information, messages and influences on the characteristics of the external world and on the control of the individual's own behavior is the senses. Therefore, the senses are considered the main channel (path) of 78 information that falls on the human body, that is, on its body organs, they carry the message about the external world and internal body organs to the contents of the large hemispheres of the brain and the cranial brain, due to which a person has the opportunity to orientate (target) the macro In the event that these channels become berk, the sensory organs do not provide the necessary information, consequently, the possibility of judging the mind disappears on its own
Keywords: internal; characteristics; external; disappears